Persistent puzzles in international finance and economics - Aggarwal, Raj (Economic & Social Studies, 2004)
As the title of this lecture suggests, I plan to talk about selected puzzles in international finance and economics. These puzzles include deviations from theoretical values that are observed in spot and forward markets in foreign exchange. Also, observed currency values persistently deviate from purchasing power and interest rate parities. Further, there is also an unexplained large home bias against international portfolio diversification, and there are frequent unexpected crashes and crises in international financial markets. These puzzles are interesting because they have not been eliminated by traders nor explained away satisfactorily by economists ? indeed their persistence challenge and intrigue us.
This paper was delivered as the Central Bank of Ireland Edgeworth Lecture, at the Eighteenth Annual Conference of the Irish Economic Association, Belfast, April 2004.
Keywords: International finance; International economics; Markets